A Daily Diary Analysis of Condom Breakage and Slippage during Vaginal Sex or Anal Sex among Adolescent Women - Hensel, Devon J. (Sex Transm Dis, 2016)
BACKGROUND: Adolescent women Adolescent women are disproportionately impacted by the adverse outcomes associated with sexual activity, including sexually transmitted infections (STI). Condoms as a means of prevention relies upon use that is free of usage failure, including breakage and/or slippage. This study examined the daily prevalence of and predictors of condom breakage and/or slippage during vaginal sex and during anal sex among adolescent women. METHODS: Adolescent women (N=387; 14 to 17 years) were recruited from primary care clinics for a longitudinal cohort study of STIs and sexual behavior. Data were daily partner-specific sexual diaries. Random intercept mixed effects logistic regression was used to estimate the fixed effect of each predictor on condom breakage/slippage during vaginal or during anal sex (Stata, 13.0), adjusting model coefficients for the correlation between repeated within-participant diary entries. RESULTS: Condom slippage and/or breakage varied across sexual behaviors and was associated with individual-specific (e.g., age and sexual interest) and partner-specific factors (e.g., negativity). Recent behavioral factors (e.g., experiencing slippage and/or breakage in the past week) were the strongest predictors of current condom slippage and/or breakage during vaginal or anal sex CONCLUSION: Factors associated with young women’s condom breakage/slippage during vaginal or during anal sex should be integrated as part of STI prevention efforts, and should be assessed as part of ongoing routine clinical care.